Pemberdayaan Remaja Putra Damarwulan Kepung Melalui Pelatihan Jahit Jilbab - Ahmad Abdul Basyir; Muhammad Faiz Amiruddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
The progress of Damarwulan village can not be separated from community participation in the empowerment of young men carried out in Damarwulan Kecamatn Village Kepung Kediri Regency. In the progress and high community participation certainly can not be separated from the shortcomings that exist in damarwulan village, therefore researchers as implementers design a program entitled "Empowerment of Young Men through Hijab Sewing". This program aims: 1) empowering young men 2) giving a work that does not yet exist in damarwulan village 3) improve the skills of young men and improve hijab sewing. This study uses the method strengthened by data obtained from interviews with the people of Damarwulan Village, Kepung District, Kediri Regency, and Mr. Aziz and brother Ainur Rouf as the owners of a place that can be damarwulan young men for hijab sewing training and from the results of practice, documentation. Data collection techniques are conducted with observations and interviews. The results of this study show that the process of empowering the youth community will look more maximal and make superior and will make young men better know what is not yet in Damarwulan Village as well as training to make hijab, the implementation of real work programs that start from August 3 to August 23, 2020 is relatively smooth. Thus, after the KKN activities ended, it is hoped that Damarwulan Village Young Men can continue to develop all the potential that has happened as well as making hijab.